Impact of entrepreneurial mindset and motivation on business performance: deciphering the effects of entrepreneurship development program (EDPs) on trainees - Santhosha Shetty G; Vikram Baliga; Mathew Thomas Gil (Cogent Business & Management, 2024)
Entrepreneurial mindset and motivation are essential for launching a successful business venture. Recognising this, the study investigates how Entrepreneurial Development Programmes (EDPs) offered by RUDSETIs (Rural Development and Self-employment Training Institutes) influence trainees in developing this mindset and motivation. Structured questionnaires were used to collect feedback from 386 unemployed trainees from three different training centres as part of a comprehensive method involving 386 unemployed trainees from three different training centres. The study has used quantitative research techniques such as the Chi-square test, Wilcoxon signed rank test, and Kruskal Wallis test to analyse the data. The findings show that EDPs have a significant positive impact on most trainees' entrepreneurial mindset, motivation, and subsequent follow-up quality. This, in turn, contributes to business success. However, a subset of trainees are unaffected by these programmes. The study raises an alarm for RUDSETIs, recommending that they increase their efforts for this specific group. Finally, the paper suggests that RUDSETI policymakers rethink and possibly reframe their current strategies. The goal should be to instill an entrepreneurial spirit, boost motivation, and improve the quality of follow-up mechanisms in order to ensure that every trainee, current or potential, benefits optimally.
Keywords: 650; Entrepreneurship; entrepreneurship mindset; motivation; follow-up; entrepreneurship development program; fostering